EVALUATION OF DRINKING WATER AUDITING SYSTEM DURING COVID 19 PANDEMIC IN IRAQ - Dr. Fateh Sadeq Alwan M.B.Ch.B, MSc.; Dr. Wafaa Ahmed Mohamed F.I.C.Ms/CM; Dr. Isra Ali Abdalla M.B.Ch.B, I.F.E.T.P (Scholar Express Journals, 2023)
Drinking water quality monitoring programs aim to support provision of safe drinking water by informing water quality management. Little evidence or guidance exists on best monitoring practices for low resource settings. Lack of financial, human, and technological resources reduce a country’s ability to monitor water supply, Water safety plans (WSP) are a comprehensive risk assessment and risk management approach that encompasses all steps in the water supply from catchment to consumer. The methods used in water treatment, such as disinfection and physical removal of pollutants, are the next lines of defense against contamination of the drinking water system after source water protection. Water Safety auditing is a crucial component of WSPs that are implemented sustainably.
Keywords: Water safety; auditing; water management system; drinking water validation